Review on Roll Pass Model for Tandem Cold Rolling Mill - Bhusana Mishra, Bibhuti (International Journal of Engineering and Technology, 2018)
Cold rolled products need strict product quality with respect to uniform gauge, good shape, and dimension. Factors affecting quality are inhomogeneous composition ofÂ Â steelÂ Â due toÂ Â non uniform distribution of alloying elements, interstand tension, and variation in pressure and co-efficient of friction. In addition to it, variation in input gauge, bending of work during roll affect quality such as flatness of the strip , uniform gauge , along the length as well as across the width. Efforts have been made in optimization of various parameters, like power consumption, mill balance control, estimation of deformation parameter and roll bending measurement and intermediate roll shifting, and finally validation through measurement. Even though there has been improvement with respect toÂ Â process automation, still there exists the need for 3D mathematical modeling of cold rolling process, with fast computational facility with huge data storage system. This paper presents the progress in this field.Â Â Â